Representasi Fashion Era Taisho-Showa pada Film Animasi Kaze Tachinu Karya Hayao Miyazaki - Megawati, Ni Luh; Sendra, I Made; Ari Sulatri, Ni Luh Putu (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 3 No 1 (2021)DO - 10.24843/JS.2021.v03.i01.p05, 2021)
This research is entitled “Fashion Representation of Taisho-Showa Era in Kaze Tachinu Animation Film by Hayao Miyazaki”. Fashion style transition from wasou to yosou was found in Taisho-Showa Era. This research aims to discover the form, function, and meaning of fashion in the Taisho-Showa era which are depicted in the film. This research used literature study method and the referral method for the data accumulation, descriptive analysis method for data analysis and for analysis results presented with informal method. For the theory, this research used literary anthropology theory by Poyatos (2008), fashion form theory by Pendergast and Tom (2004), fashion function theory by Barnard (1996), and semiotics theory by Barthes (1964). Based on the analysis results, can be seen that fashion’s form that represent in Taisho-Showa era are divided into two category, first is wasou which consists of hakama, haori, kimono, mandarin shirt, obi, shimada, comb, geta, tabi, and zori, and the second one is yosou that consists of men’s suit, stockings, trench coat, men’s hats, short hair for woman, waved hair for woman, clutch purse, patent leather shoes, and high heeled boots. For the fashion’s function that found in this research are 1) protection function; 2) politeness and concealment function; 3) communication function; 4) individualistic expression; 5) social worth or status; 6) economic worth or status; 7) magical-religious condition; and 8) recreational functions. And for the fashion’s meaning in the Taisho-Showa era, in denotation is refers to the form and design of fashion, while the connotation of fashion is formed by the influence of social and cultural values in Japanese society.